2019
DOI: 10.15406/mojgg.2019.04.00170
|View full text |Cite
|
Sign up to set email alerts
|

Development of the family support scale (FSS) for elderly people

Abstract: The situation of elderly people is an increasingly pressing global concern. This issue is especially challenging for developing countries, where, traditionally, the majority of the elderly people have lived with their family and have been dependent on family support. Nowadays, however, appropriate family support is no longer guaranteed. An assessment tool for measuring active family support would be useful for describing the real living situation of the elderly. The purpose of this study was to develop an acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 10 publications
0
8
0
1
Order By: Relevance
“…Responsiveness, standard error, interpretability, ceiling and floor effects, and ease of the FSOP questionnaire were within acceptable ranges. Other similar questionnaires in international literature have not reported on these psychometric criteria (27,28,36).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Responsiveness, standard error, interpretability, ceiling and floor effects, and ease of the FSOP questionnaire were within acceptable ranges. Other similar questionnaires in international literature have not reported on these psychometric criteria (27,28,36).…”
Section: Discussionmentioning
confidence: 95%
“…Uddin and Bhuiyan ( 27 ) and Tselebis et al ( 36 ) developed family support scales for older people, but they did not conduct factor analysis as the most important aspect of evaluating psychometric properties. The factor analysis process of the FSOP questionnaire showed that some items had more factor burden and were therefore more important in assessing the validity of the related domains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Question items for three exogenous variables, namely perceived income adequacy for current needs, perceived income adequacy for current wants, and financial anxiety adopted from the Sears study (2008). Meanwhile, the question item for the perceived family support variable refers to the research of Uddin and Bhuiyan (2019), Komjakraphan et al (2009), and Kyzar et al (2012). The study's endogenous variable is tax non-compliance, with the question item adapted from Kasipillai and Abdul-Jabbar (2006) and Aregbesola et al (2020).…”
Section: Methodsmentioning
confidence: 99%
“…The family support scale (FSS) for elderly people comprises 20 items to assess perceived support for the following 20 areas: company, daily activities, emotional support, food, happiness, health, help in problem-solving, important decisions, important people, information, love, money, personal needs, personal problems, religious activities, respect, satisfaction, sleep, social events, and treatment. 56 Each item is measured on a 4-point Likert scale from 0 (no) to 3 (much). 56 The total possible scores fall between 0 and 60, where a higher score reflects greater perceived family support for the elderly.…”
Section: Methodsmentioning
confidence: 99%